“Diseño de un plan integrado de emergencias en la escuela superior militar "eloy alfaro" quito, 2021” - López Villacres, Melissa Andreina (2021)
The present research work had as its goal the design of an integrated emergency plan in the "Eloy Alfaro" High School (ESMIL), which refers to two variables: the emergency plan and the reduction of fire risks in case of an emergency that arises over the years. The objectives were established on the basis of information gathering that led to the problem: There is no emergency plan as such, but contingency plans for specific areas. This gave way to the first objective established, which is the identification of risk zones in the different work areas, which was carried out through GTC 45, then evaluated through matrices such as risk analysis, vulnerability and threats and diamond matrix which gave a conclusion that was the risk of fire and applied the Meseri and Gretener which are more specific evaluations with this gave way to the last objective which is the creation of the contingency plan based on fires in areas identified with imminent risk. The topics covered in the research were contingency plans for fires, risks and dangers, the Eloy Alfaro military high school was evaluated in general with a total of 28 areas in order to find which were its vulnerability, its structure, its building and the resources at hand, using the Meseri and Gretener methods it was possible to identify which were the areas most susceptible to the formation of fires that could be dangerous for the population itself in this case the areas of the warehouse of the quartermaster: evaluated by Meseri 4.76, grand parade: 4.69, grand parade: 4.69, and the areas of the warehouse of the quartermaster: evaluated by Meseri 4.76. 76, grand parade: 4.69, auto center and workshops: 4.3; evaluated by Gretener kitchen boilers: 0.45, swimming pool: 0.59 and cadet dormitories: 0.34, which showed a high risk in the evaluations carried out. Finally, a contingency plan was prepared based on fires, where the most serious areas detected were evaluated in order to support the prevention measures within these areas and to know how to act and what to do if something were to happen, such as a fire that has already been caused or is developing naturally. The contingency plan established the necessary brigades for these specific areas where there could be a risk of fire, preventive measures for the affected areas, summary evaluations and ESMIL's resources. KEY WORDS: emergency, contingency, matrix, meseri, gretener, preventive measures